Oil-soluble water control particle, micro-nano oil-soluble water control particle system for oil field and preparation method of micro-nano oil-soluble water control particle system

By developing micro-nano-scale oil-soluble water-control particles, and using emulsion polymerization to generate an oil-in-water emulsion dispersion system, the problem of early water and high water content in offshore oil fields is solved, selective water control is achieved, and oil field development efficiency is improved.

CN119529168APending Publication Date: 2025-02-28CNOOC ENERGY TECHNOLOGY & SERVICES LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411617959.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-28

Smart Images

  • Figure CN119529168A_ABST
    Figure CN119529168A_ABST
Patent Text Reader

Abstract

The invention discloses an oil-soluble water control particle, a micro-nano oil-soluble water control particle system for an oil field and a preparation method of the micro-nano oil-soluble water control particle system. The micro-nano oil-soluble water control particle system comprises the following raw materials in percentage by mass: 12-25wt% of oil-soluble water control particles and the balance of water, 5-8 wt% of white oil; 4-6 wt% of a dispersant A; 1.3-2 wt% of a dispersant B; and the balance of water. The water control system provided by the invention has good reservoir injectability and excellent selective water control performance of plugging when encountering water and dissolving when encountering oil, can be used for independently carrying out water control operation, and can also be used as a slug of completion fluid and workover fluid. The development of the material can fill up chemical water control means of an oil field to a certain extent, guide and improve a process system and enrich water control methods, so that the development effect is improved, and a new thought is provided for the oil field water control technology in the future.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of oil and gas development, and in particular to an oil-soluble water-controlling particle, a micro-nano oil-soluble water-controlling particle system for oil fields and a preparation method thereof. Background Art

[0002] After years of exploration and development, offshore oil fields have entered the middle and late stages of development. Affected by geological reservoir factors, there are a large number of low-yield and low-efficiency wells, with a comprehensive water content of 79%. The water content of a few oil fields is even as high as 95% or more, of which high-water-content oil wells account for 26.7% of the total number of low-yield and low-efficiency wells. Early water breakthrough and high water content are the main reasons for the low production and low efficiency of oil wells. Most offshore oil fields have bottom water or edge water, high oil well production capacity and large production pressure difference. Water is more likely to invade oil wells from highly heterogeneous high-permeability channels. After the formation water breakthrough occurs in the oil well, the oil production will be greatly reduced, which seriously affects the normal economic development indicators. The demand for water control in oil fields is becoming increasingly urgent.

[0003] At present, the water control methods of offshore oil fields mainly adopt measures from two aspects: water wells and oil wells. Water wells are adjusted to suppress injection water cross-flow and reduce the water content of oil wells. Water control in oil wells is mainly carried out through completion (wellbore) and formation water control. Offshore oil fields have successively adopted a variety of completion water control technologies, including ICD, AICD, and continuous packer technology, with obvious water control effects. However, mechanical water control is mainly used for water layer plugging, with complex construction technology and high comprehensive cost. It requires accurate understanding of wellbore water breakthrough, which is difficult to apply to stable production and potential tapping of old oil fields and staggered thin-layered distribution oil reservoirs; formation water control mainly relies on the plugging agent system. At present, chemical water control mostly uses gel and jelly plugging agents. This type of plugging agent has poor selectivity, high injection pressure, residual after screening, and great reservoir damage. Selective chemical plugging agents such as foam, heavy oil, and hydrolyzed polyacrylamide have short effective periods, poor high temperature resistance, low efficiency, and high construction risks, and may even cause oil wells to be blocked.

[0004] In summary, the main problems of chemical profile control and water plugging agents that need to be solved in oil and gas field development are:

[0005] 1) At present, the strength or particle size of most chemical water control agents is poorly matched with the reservoir pore throat, resulting in poor injectability of the agents;

[0006] 2) Mechanical water control and ICD lack chemical water control agents to transform the reservoir, and cannot be regulated at a deeper level from the reservoir. In addition, chemical water control agents are usually not very selective and have a significant plugging effect on both the oil and water phases. It is urgent to develop selective water plugging and profile control agents;

[0007] 3) Chemical water control agents and process technologies for high temperature (above 120°C) deep wells (above 5000m) are immature, and the mechanical water finding and plugging technology for multi-layer vertical wells and long horizontal sections of horizontal wells is complex. There is an urgent need for a water control system that is resistant to high temperature, high mineralization, and has a relatively simple construction process.

[0008] Therefore, in view of the characteristics of multi-layer co-production, oil and water in the same layer, and screen completion in offshore oil fields, it is necessary to adopt a polymer synthesis process to develop a micro-nano oil-soluble material that has good injectivity not only in reservoirs with different permeability but also in completion screens of different sizes; this nano material must have good reservoir injectivity and excellent selective water control performance of plugging when encountering water and dissolving when encountering oil. It can be used alone for water control operations or as a plug for working fluids. The development of this material can fill the gap in chemical water control means in offshore oil fields to a certain extent, guide the improvement of process systems, enrich water control methods, thereby improving development effects, and provide a new idea for future offshore oil field water control technology. Summary of the invention

[0009] In order to solve the above technical problems, the present invention provides an oil-soluble water-controlling particle, a micro-nano oil-soluble water-controlling particle system for oil fields and a preparation method. The system is a water-in-oil emulsion system, in which the synthesized oil-soluble particles are dissolved in an oil phase solvent and wrapped in a water phase. Different emulsification conditions make the particle size distribution of the emulsified particles range from nanometers to micrometers, so that it can meet the injectability of different reservoir permeabilities. After the system reaches the target reservoir, it breaks the emulsion, releases the oil phase, and the particles are adsorbed on the reservoir pore throats to form a bridge. Under the influence of the reservoir temperature, due to the lipophilic and hydrophobic nature of the particles themselves, they do not dissolve in water in the pore throats, and can gradually soften and dissolve in the oil phase after encountering oil, thereby exerting a selective water control effect.

[0010] In a first aspect, the present invention provides an oil-soluble water-controlling particle, which is realized by adopting the following technical solution.

[0011] An oil-soluble water-controlling particle, the structural formula of the oil-soluble water-controlling particle is as follows:

[0012]

[0013] Wherein, m=90-256; n=45-128; "*" represents a free radical.

[0014] Furthermore, the average molecular weight of the oil-soluble water-controlling particles is 50,000 to 100,000.

[0015] In a second aspect, the present invention provides a method for preparing oil-soluble water-controlling particles, which is achieved by adopting the following technical scheme.

[0016] A method for preparing the above-mentioned oil-soluble water-controlling particles is characterized by comprising the following steps:

[0017] 35-45% by mass of octadecyl methacrylate and methyl methacrylate (35-45% by mass is the proportion of the total mass of octadecyl methacrylate and methyl methacrylate), 3%-5% of Span-80 and 3%-5% of Tween-80 are added in sequence, and after complete dissolution, a pH adjuster is added to adjust the pH value to 6.5-7.5, and the stirring speed is fixed at 500 rpm and stirred until the reaction system is full of foam; the mixed solution is heated to 30-50° C. and N2 is introduced. After 0.5-1h, the introduction of N2 is stopped and the mixed solution is heated to 75-90° C.; then, a redox system accounting for 0.7-0.9% by mass of the monomer and 0.1%-0.2% of an azo initiator are added dropwise, and the dropping time is controlled within 1 hour; after the dropwise addition is completed, the mixture is stirred at 75-90° C. for 5-8 hours to obtain oil-soluble water-controlling particles.

[0018] The reaction formula is as follows:

[0019]

[0020] Wherein, m=90-256; n=45-128; "*" represents a free radical.

[0021] Furthermore, the molar ratio of octadecyl methacrylate to methyl methacrylate is 2:1 to 3:1.

[0022] Furthermore, the pH adjuster is selected from one of hydrochloric acid, oxalic acid, sodium hydroxide and sodium bicarbonate.

[0023] Furthermore, the redox system is selected from one or more of ammonium persulfate, ammonium bisulfite, sodium bisulfite, and potassium persulfate.

[0024] By adopting the above technical scheme, the synthesized oil-soluble water-controlling particles have good oleophilic and hydrophobic properties. After adding the material to the surface of the core slice, the wettability can be changed from water-philic to oil-philic, that is, the oil phase contact angle is significantly reduced, while the water phase contact angle is significantly increased. After the treatment, the average oil phase contact angle of the core slice is 25.616°, and the average water phase contact angle is 123.943°, which reflects the oleophilic and hydrophobic properties of the material.

[0025] In addition, the synthesized oil-soluble particles have good oil-phase solubility and water-phase insolubility. In the oil-phase solvent, the polymer particle chain segments elongate and stretch after absorbing oil, and gradually dissolve in the oil phase after saturation; in the water phase, the polymer chain segments are aggregated and cannot absorb the water-phase liquid, showing good "oil-soluble and water-soluble" characteristics as a whole.

[0026] In a third aspect, the present invention provides a micro-nano oil-soluble water-controlling particle system for oil fields, which is achieved by adopting the following technical solutions.

[0027] A micro-nano oil-soluble water-controlling particle system for oil fields comprises the following raw materials in percentage by weight: 12-25 wt% of the above-mentioned oil-soluble water-controlling particles; 5-8 wt% of white oil; 4-6 wt% of dispersant A; 1.3-2 wt% of dispersant B; and the balance is water.

[0028] Furthermore, the white oil is one of 40# or 60# white oil or a mixture of the two in any ratio.

[0029] Furthermore, the dispersant A is selected from one of Span-80, oleic acid, and lauric acid polyoxyethylene ether LAE-4.

[0030] Furthermore, the dispersant B is selected from one of Tween-80, triethanolamine and sodium dodecylbenzene sulfonate.

[0031] In a fourth aspect, the present invention provides a method for preparing a micro-nano oil-soluble water-controlling particle system for oil fields, which is achieved by adopting the following technical scheme.

[0032] A method for preparing the above-mentioned micro-nano oil-soluble water-controlling particle system for oil fields comprises the following steps:

[0033] Dissolve a specified amount of oil-soluble particles in white oil and add dispersant A to form a certain amount of oil phase system, stir evenly and set aside;

[0034] Add dispersant B to a specified amount of water to form an aqueous phase system, and stir evenly for use;

[0035] The oil phase is placed at a dispersion temperature and stirred at a high speed at a certain rotation speed. After 0.5 to 1 hour, the water phase is slowly dripped into it and stirring is continued for 2 to 3 hours to obtain a micro-nano oil-soluble water-controlling particle system.

[0036] Furthermore, the dispersion temperature is 70 to 90°C.

[0037] Furthermore, the high-speed stirring speed is 2000-15000 rpm.

[0038] By adopting the above technical solution, the median particle size range of the oil-soluble particles can be adjusted to 400nm~1.5μm according to different dispersion conditions after being dispersed in the water phase. The oil-soluble water-control particle system of the present application is applied to oilfield water control operations. After being injected into the reservoir, the oil-soluble particle polymer needs to be released under reservoir conditions. The particles are adsorbed, accumulated, and fused in the pore throats of the reservoir, and the selective water control effect is exerted by utilizing their own "oil-soluble but water-insoluble" characteristics. Therefore, the system has the characteristic of releasing oil-soluble particles by rupturing the outer membrane under reservoir conditions.

[0039] The oil-soluble water-control particle system of this application has good injectability, oil-water selectivity and scour resistance in the reservoir. In the laboratory evaluation, the injection pressure is less than 1MPa when stable; the water phase permeability after plugging is significantly higher than the original water phase permeability before plugging, while the oil phase permeability remains basically unchanged, the water phase permeability plugging rate is greater than 80%, and the oil phase permeability plugging rate is less than 20%, so it can be seen that the water control system has good selectivity; when the system is flushed in the core by more than 20PV, the system's selective water control performance remains unchanged, and it has good scour resistance.

[0040] This application has the following beneficial effects.

[0041] The oil-soluble water-controlling particles of the present invention are generated by emulsion polymerization, and a water-in-oil emulsion dispersion system is formed by emulsification dispersion. The oil-soluble particles are dissolved in the oil phase solvent and wrapped in the water phase. The median distribution of the particle size is 0.4-1.5 μm, so that they can smoothly reach the reservoir pore throat during construction, and demulsify under the conditions of reservoir temperature and salinity, releasing the oil phase, and the particles are adsorbed on the reservoir pore throat to form a bridging effect. After contacting the reservoir fluid, due to the lipophilic and hydrophobic properties of the particles, the effect of blocking water without blocking oil is achieved. In addition, the preparation method of the present invention is simple, the reaction conditions are mild, the operation is convenient, and it is easy to industrialize production. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 This is a test diagram of the water contact angle on the surface of the core slice after being treated with the oil-soluble water-controlling particles in Example 1 of the present invention;

[0043] Figure 2 This is a test diagram of the oil phase contact angle on the surface of the core slice after being treated with the oil-soluble water-controlling particles in Example 1 of the present invention;

[0044] Figure 3 This is a scanning electron microscope side view of the oil-soluble water-controlling particles after oil absorption in Example 1 of the present invention;

[0045] Figure 4 This is a test chart of the median particle size of Example 1 of the present invention;

[0046] Figure 5 This is a test chart of the median particle size of Example 2 of the present invention;

[0047] Figure 6 This is a test chart of the median particle size of Example 3 of the present invention;

[0048] Figure 7 This is a test diagram of injectability in an artificial core of Example 1 of the present invention;

[0049] Figure 8 This is a test diagram of the plugging performance of the water phase in the artificial core of Example 1 of the present invention;

[0050] Fig. 9This is a test diagram of the plugging performance of the oil phase in the artificial core in Example 1 of the present invention;

[0051] Fig.10 This is a test diagram of the scour resistance of Example 1 of the present invention in an artificial rock core. DETAILED DESCRIPTION

[0052] The present patent application is further described below in conjunction with embodiments.

[0053] The oil-soluble water-controlling particle system developed by the present invention uses octadecyl methacrylate and methyl methacrylate as comonomers, adopts emulsion polymerization to synthesize oil-soluble water-controlling particles, and forms a water-in-oil emulsion dispersion system through emulsification dispersion. The oil-soluble particles are dissolved in the oil phase solvent and wrapped in the water phase, so that they can smoothly reach the reservoir pore throat during construction, and demulsify under the conditions of reservoir temperature and salinity, releasing the oil phase, and the particles are adsorbed on the reservoir pore throat to form a bridging effect. After contacting the reservoir fluid, due to the lipophilic and hydrophobic properties of the particles, the effect of blocking water without blocking oil is achieved.

[0054] Example 1

[0055] A method for preparing a micro-nano oil-soluble water-controlling particle system for oil fields comprises the following steps:

[0056] In a four-necked flask, 40 g of octadecyl methacrylate and 5 g of methyl methacrylate, 5 g of Span-80 and 5 g of Tween-80 were added in sequence, and then deionized water was added to prepare a 100 mL solution. After complete dissolution, NaHCO3 solution was added to adjust the pH value to 7.5, and a high-speed stirrer was used to fix the stirring speed at 500 rpm and stirred until the four-necked flask was full of foam; after complete dissolution, it was placed in a 30°C water bath for heating and N2 was introduced for protection. After half an hour, the nitrogen bottle was closed and the mixed solution was heated to 80°C; then 0.405 g of ammonium bisulfite (0.119 g) and sodium persulfate (0.286 g) and 0.009 g of 2,2'-azobisisobutylamidine dihydrochloride (V50) were dissolved in 5 mL of water, and added dropwise (within 1 hour); after stirring at 80°C for 8 hours, a polymer was obtained, which was the oil-soluble water-controlling particles in the present invention.

[0057] Dissolve 25g of oil-soluble particles in 8mL of 40# white oil and add 6g of oleic acid, stir evenly and set aside; add 2g of triethanolamine to 60mL of tap water, stir evenly and set aside; place the oil phase at a dispersion temperature of 80°C and stir at a speed of 15000rpm, slowly drip into the water phase after 0.5h, and continue stirring for 2h to obtain the configured micro-nano oil-soluble water-controlling particle system.

[0058] The state of the oil-soluble water-controlling particles obtained in Example 1 in white oil was observed using an electron microscope. The results are as follows: Figure 3 It can be observed that the polymer chain segments of the oil-soluble water-control particles in the white oil are stretched and elongated after absorbing the oil, and the chain segment spaces are filled with the white oil to reach the saturated oil state, reflecting good oil-soluble properties.

[0059] Example 2

[0060] A method for preparing a micro-nano oil-soluble water-controlling particle system for oil fields comprises the following steps:

[0061] In a four-necked flask, 36.4 g of octadecyl methacrylate and 3.6 g of methyl methacrylate, 3.5 g of Span-80 and 3.5 g of Tween-80 were added in sequence, and then deionized water was added to prepare 100 mL of solution. After complete dissolution, NaHCO3 solution was added to adjust the pH value to 7, and a high-speed stirrer was used to fix the stirring speed at 500 rpm and stirred until the four-necked flask was full of foam; after complete dissolution, it was placed in a 40°C water bath for heating and N2 was introduced for protection. After half an hour, the nitrogen bottle was closed and the mixed solution was heated to 85°C; then 0.32 g of potassium bisulfite (0.115 g) and sodium persulfate (0.205 g) and 0.008 g of 2,2'-azobisisobutylamidine dihydrochloride (V50) were dissolved in 5 mL of water, and added dropwise (within 1 hour); after stirring at 90°C for 7 hours, a polymer was obtained, which was the oil-soluble water-controlling particles of the present invention.

[0062] Dissolve 20g of oil-soluble particles in 6mL of 40# white oil and add 5g of Span-80, stir evenly for use; add 1.5g of Tween-80 to 50mL of tap water, stir evenly for use; place the oil phase at a dispersion temperature of 85°C and stir at a speed of 10000rpm, slowly drip into the water phase after 0.5h, and continue stirring for 2h to obtain the configured micro-nano oil-soluble water-controlling particle system.

[0063] Example 3

[0064] A method for preparing a micro-nano oil-soluble water-controlling particle system for oil fields comprises the following steps:

[0065] In a four-necked flask, 31.8 g of octadecyl methacrylate and 3.2 g of methyl methacrylate, 3 g of Span-80 and 3 g of Tween-80 were added in sequence, and then deionized water was added to prepare a 100 mL solution. After complete dissolution, NaHCO3 solution was added to adjust the pH value to 7, and a high-speed stirrer was used to fix the stirring speed at 500 rpm and stirred until the four-necked flask was full of foam; after complete dissolution, it was placed in a 45°C water bath for heating and N2 was introduced for protection. After half an hour, the nitrogen bottle was closed and the mixed solution was heated to 80°C; then 0.28 g of potassium bisulfite (0.101 g) and sodium persulfate (0.179 g) and 0.006 g of 2,2'-azobisisobutylamidine dihydrochloride (V50) were dissolved in 5 mL of water, and added dropwise (within 1 hour); after stirring at 85°C for 6 hours, a polymer was obtained, which was the oil-soluble water-controlling particles in the present invention.

[0066] Dissolve 30g of oil-soluble particles in 10mL of 60# white oil and add 4g of lauric acid polyoxyethylene ether LAE-4, stir evenly for use; add 3g of sodium dodecylbenzene sulfonate to 50mL of tap water, stir evenly for use; place the oil phase at a dispersion temperature of 85°C and stir at a speed of 8000rpm, slowly drip into the water phase after 0.5h, and continue stirring for 2h to obtain the configured micro-nano oil-soluble water-controlling particle system.

[0067] Performance Testing

[0068] 1. Contact angle measurement

[0069] Experimental determination method: The contact angle was determined in accordance with GB / T 24368-2009 Contact angle measurement method for detecting hydrophobic contaminants on glass surface. First, the water phase and oil phase contact angles of the untreated core slices were tested (the water phase was tap water and the oil phase was kerosene); then the oil-soluble water-controlling particle system in Examples 1 to 3 was added dropwise to the surface of the core slices, and the water phase and oil phase contact angles of the treated core slices were tested after high-temperature aging at 90°C. The test results are shown in Tables 1 and Figure 1-2 .

[0070] Table 1 Changes in contact angles of water and oil phases before and after treatment in Examples 1-3

[0071]

[0072] The test results show that after the core slice is treated with the oil-soluble water-controlling particle system, the water phase contact angle increases significantly and can reach more than 100°; the oil phase contact angle decreases to about 30°. Therefore, it can be seen that the oil-soluble water-controlling particle system has good oleophilic and hydrophobic properties.

[0073] 2. Determination of median particle size

[0074] Experimental test method: The median particle size was analyzed using a Malvern Mastersizer 3000 laser particle size analyzer. 0.1 mL of the oil-soluble water-controlling particle system in Examples 1 to 3 was placed in a sample pool at room temperature. After the sample was evenly dispersed, pure water was added to the sample. After removing the liquid bubbles, the particle size test was performed. The average value was taken after repeating the measurement three times, which was the median particle size. The test results are shown in Tables 2 and Figure 4-6 .

[0075] Table 2 Particle size median test results of the embodiment

[0076]

[0077] The test results show that the particle size in the oil-soluble water-controlling particle system can reach the micro-nano level and can be adjusted according to different preparation conditions.

[0078] 3. Core injectivity determination

[0079] Experimental test method: The oil-soluble water-controlling particle system in Example 1 was configured into a solution system with a mass fraction of 30%, and injected into the artificial sandstone core with a permeability of 1500mD at room temperature at a flow rate of 1mL / min. The final stable injection pressure during the injection process was measured. The test results are shown in Figure 7 .

[0080] The test results show that the injection pressure of the system configured in Example 1 gradually increases with the increase of injection volume. When the injection volume is about 3.5PV, the injection pressure begins to stabilize and reaches about 0.7MPa. The injection pressure no longer increases with the increase of injection volume. Therefore, it can be seen that the system has good injectability in the core.

[0081] 4. Oil-water selectivity determination

[0082] Experimental test method: The oil-soluble water-controlling particle system in Example 1 is configured into a solution system with a mass fraction of 30%, and two artificial sandstone cores with a permeability of 1500mD, a diameter of 25mm, and a length of 8cm are taken and dried. Take the dried 1# core, inject the fluid (simulated formation water or formation water) forward from one end of the core at a flow rate of 1mL / min, and stop the injection when the injection pressure is stable, and calculate the original water phase permeability K1; then reversely inject the system into the core at a flow rate of 1mL / min, and continue to displace 2~3PV after the injection pressure is stable, and then stop. The core injected with the system is aged at the reservoir temperature (90℃) for 24~48h; take the aged core, displace the simulated formation water forward, and stop the injection when the pressure is stable, and calculate the water phase permeability K2 after plugging. After the water phase displacement test is completed, the 2# core is tested using simulated oil (3# white oil), and the original permeability of the oil phase and the permeability of the oil phase after plugging are tested and calculated. The oil-water selectivity of the system is evaluated by the changes in the permeability of the water phase and the oil phase before and after injection into the core. The more the water phase permeability decreases, the stronger the water control ability of the water control proppant; the less the oil phase permeability decreases, the stronger the oil-water selectivity of the water control proppant. Figure 8 , Fig. 9 and Table 3.

[0083] Table 3

[0084]

[0085] The experimental results show that the water phase pressure after plugging tends to be stable after displacing 12.7PV, which is 0.0338MPa, much higher than the original water phase pressure of 0.0057MPa; while the oil phase stable pressure after plugging is 0.0199MPa, which is basically unchanged compared with the original oil phase pressure of 0.0190MPa. Through calculation, the water phase permeability after plugging is significantly higher than the original water phase permeability before plugging, which has decreased by 82.46%, while the oil phase permeability is basically unchanged, which has only decreased by 7.35%. Therefore, it can be seen that the selectivity of the water control system is good.

[0086] 5. Determination of erosion resistance

[0087] Experimental test method: The oil-soluble water-controlling particle system in Example 1 is configured into a solution system with a mass fraction of 30%. Two artificial sandstone cores with a permeability of 1500mD, a diameter of 25mm, and a length of 8cm are taken and dried. Take the treated artificial sandstone cores, use formation water as the fluid to saturate the cores, and then inject them into the system. The test method is the same as the oil-water selectivity test; after the core is aged, simulated formation water is injected in reverse at a flow rate of 1mL / min to observe the change in displacement pressure to evaluate the scour resistance of the system. The experimental results are as follows: Fig.10 shown.

[0088] In order to maintain the long-term effectiveness of the water control system in the reservoir, it is necessary to have good scour resistance during the oil well production process to extend the water control time of the water control system. Therefore, the scour resistance of the system in the core was evaluated indoors. It can be seen from the experimental results that when the aged core is plugged with water phase displacement, the displacement pressure increases and then gradually decreases with the increase of displacement fluid. When the displacement fluid is injected to 12.5PV, the displacement pressure gradually stabilizes, and when the displacement volume reaches 25PV, the pressure remains above 0.032MPa without decreasing. Therefore, the system is evaluated to have good scour resistance.

[0089] The embodiments of this specific implementation method are all preferred embodiments of the present invention, and are not intended to limit the protection scope of the present invention. Therefore, all equivalent changes made based on the structure, shape, and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. An oil-soluble water-controlling particle, characterized in that: The structural formula of oil-soluble water-controlling particles is as follows: Among them, m=90-256; n=45-128.

2. The oil-soluble water-controlling particle according to claim 1, characterized in that: The average molecular weight of the oil-soluble water-controlling particles is 50,000 to 100,000.

3. A method for preparing the oil-soluble water-controlling particles according to claim 1 or 2, characterized in that: The following steps are involved: 35-45% of octadecyl methacrylate and methyl methacrylate, 3%-5% of Span-80 and 3%-5% of Tween-80 are added in sequence, and after complete dissolution, a pH adjuster is added to adjust the pH value to 6.5-7.5, and the stirring speed is fixed at 500 rpm and stirred until the reaction system is full of foam; the mixed solution is heated to 30-50° C. and N2 is introduced. After 0.5-1h, the introduction of N2 is stopped and the mixed solution is heated to 75-90° C.; then, a redox system accounting for 0.7-0.9% of the monomer mass fraction and 0.1%-0.2% of an azo initiator are added dropwise, and the dropping time is controlled within 1 hour; after the dropwise addition is completed, stirring is performed at 75-90° C. for 5-8 hours to obtain oil-soluble water-controlling particles.

4. The method for preparing an oil-soluble water-controlling particle according to claim 3, characterized in that: The molar ratio of octadecyl methacrylate to methyl methacrylate is 2:1 to 3:

1.

5. A micro-nano oil-soluble water-controlling particle system for oil fields, characterized by: The invention comprises the following raw materials in percentage by weight: 12-25 wt% of the oil-soluble water-controlling particles according to claim 1 or 2; 5-8 wt% of white oil; 4-6 wt% of dispersant A; 1.3-2 wt% of dispersant B; and the balance is water.

6. The micro-nano oil-soluble water-controlling particle system for oil fields according to claim 5, characterized in that: The white oil is one of 40# or 60# white oil or a mixture of the two in any ratio.

7. The micro-nano oil-soluble water-controlling particle system for oil fields according to claim 5, characterized in that: The dispersant A is selected from one of Span-80, oleic acid, and lauric acid polyoxyethylene ether LAE-4.

8. The micro-nano oil-soluble water-controlling particle system for oil fields according to claim 5, characterized in that: The dispersant B is selected from one of Tween-80, triethanolamine and sodium dodecylbenzene sulfonate.

9. A method for preparing the micro-nano oil-soluble water-controlling particle system for oil fields according to any one of claims 5 to 8, characterized in that: The following steps are involved: Dissolve a specified amount of oil-soluble particles in white oil and add dispersant A to form a certain amount of oil phase system, stir evenly and set aside; Add dispersant B to a specified amount of water to form an aqueous phase system, and stir evenly for use; The oil phase is placed at a dispersion temperature and stirred at a high speed at a certain rotation speed. After 0.5 to 1 hour, the water phase is slowly dripped into it and stirring is continued for 2 to 3 hours to obtain a micro-nano oil-soluble water-controlling particle system.